PENERAPAN MODEL PEMBELAJARAN ROLE PLAYING UNTUK MENINGKATKAN KEMAMPUAN BERMAIN DRAMA PADA SISWA KELAS V SDN NAGRAK LEMBANG TAHUN PELAJARAN 2012/2013 - Eka Suprapriyadi, Yudi; Ariyanto Purnomo, Arip (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2016)
Playing the drama is learning that can foster creativity, attitude, character, confidence, courage to face a lot of people, responsible, and has the soul of art. With the model of role playing can train students' understanding and creativity in living up to its role in the story. This study aims to determine the ability of authors and students in learning to play the drama by using model role playing Then, to determine the effectiveness of learning to do plays with role playing learning model used in Class V SDN Nagrak Lembang. Based on this research, the authors can conclude the following. The results of students of class V SDN Nagrak Lembang, able to play drama. This can be evidenced from the average value of 50 pretest, posttest average value of 85. The difference between pretest and posttest is 35. From the average value of the performance to-1 by 58 and the value of the average performance of all 2 at 84. the difference between the performance of the 1st and 2nd performance is 26. This value indicates that the class V students of SD Negeri Nagrak Lembang able to do plays well. Model role playing effectively used in learning to play the drama students of class V SDN Nagrak Lembang. This is evident from the results of statistical calculation and results of calculation of the significant level of pretest and posttest differences mean that t_hitung> t_tabel, namely 46.54> 33.15, the 95% confidence level and degrees of freedom 34. That is, the method used in the effective role playing learning to play role.